The correlation between identifying needs and choosing the appropriate productive art for use / primary health care centers as an example - Mahmood, Zinah Muayad; Mohammed, Mohammed Jasim (Journal of Economics and Administrative Sciences, 2020)
The purpose of the study is to identify the need to improve health services in Iraq by determining the efficiency of service in health care centres and working on exploiting limited resources through choosing the most efficient technological art represented by using precast concrete technology to fill the shortfall in the establishment health centres for primary care and to explain the impact of this on saving resources, time, and increasing production efficiency. To achieve this, the quantitative analysis adopted as a methodology in the study by determining the size of the deficit in the infrastructure of health centres for primary care according to the standard of a health centre / 10.000 people with an estimate of the future need for the next ten years depending on the population growth rate estimated by (2.6%). In addition to exploiting the available resources and achieving stability for the population by providing productive employment opportunities within the medium and long term. This makes the study distinguished by originality, as it linked the diagnosis of the problem of finding solutions using the modern technical method that encourages private investment.Paper type: Technical paper.